Petrology and geochemistry of amphibole-bearing melagranite from Taiping Pluton, North of Peninsular Malaysia / Quek Long Xiang - Quek, Long Xiang (2015)
Taiping pluton is an N-S elongated pluton located in the Bintang batholith. This batholith together with Main Range batholith, represent most of the granitoid within the Main Range granite province of Peninsular Malaysia. The Taiping amphibole-bearing melagranite, also known as the Buloh Pelang granite was briefly studied before. It is only recently, ultrapotassic “durbachite” type characteristics are found in these rocks. Taiping melagranite can be described as K-Mg rich, megacrystic to porphyritic, coarse grained, dark colored granite. Petrographic examination shows the rocks contain granite felsic mineral proportion with high amount of biotite, amphiboles (actinolite) with pyroxene relics and traces of pyroxene. The melagranite also contain mutliple mafic microgranular enclaves of various sizes. Most melagranite samples are ultrapotassic and intermediate in SiO2 composition while showing high MgO and Cr. They are also high in certain incompatible elements (Ba, Zr, Rb, Th) and LREE. In general, the melagranite geochemistry is comparable to the Central European durbachite suite. The “durbachite” type melagranite petrogenesis is believed to be complex, requiring a crustal component and enriched lithospheric mantle source. The enrichment process could have been contributed by a previous subduction event. The Taiping pluton itself is located in the Sibumasu plate (which subducted under the Indochina plate before the collision) and U-Pb zircon dating results (218 ± 1.3 Ma) indicate that they are emplaced during the Triassic Sibumasu-Indochina collision (200 – 220 Ma), when most of the Main Range granite province are emplaced. To fit into the current tectonic model, I believe a minor episode of extension could have occurred during early contraction. As the plates continue to converge, compressive tectonic regime was re-established.